Existing relationship between types of leadership leadership and achievements of learning in basic municipalized schools belonging to Antofagasta Municipal Social Corporation - Díaz Asencio, Ricardo Javier (2019)
To the question of what to investigate, this study considered the question of Does the headmaster / headmistress’ style have any influence or not in students’ learning achievements. Using SIMCE evaluation in Fourth Graders as a reference to solve this question, overall the score interpretations of this test applied between 2012 and 2016 in Mathematics and Reading Comprehension sections. The results were taken from Simce webpage and they are part of public knowledge politics, however is not possible to find and determine leadership’s styles, which were obtain from results of surveys directed to a different variety of headmasters and mistresses from schools that belong to Antofagasta CMDS, selected at random, using Blake and Mouton Leadership Style Test. This test is an Aroldo David Noriega’s free translation, which can be found in an open internet platform. The crossing of this data becomes the indicators to develop the hypothesis that headmaster’s / headmistresses’ leadership style v/s student’s academic results, concluding that this hypothesis cannot be verified in 100%, due to the results of an external evaluation and results obtained through a survey do not show clarity of such hypothesis, in many cases, results were positive but not steady in time.